Analisis Permasalaan Diri terhadap Kemampuan Siswa Sekolah Dasar (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to examine self-confidence issues in elementary school students, particularly second-grade students at SDN 1 Gulang. Various problems identified included shyness, low self-confidence, fear of performing in front of the class, and a tendency to withdraw from social settings. This study used a qualitative approach with data collection techniques including interviews and observations to identify factors contributing to low self-confidence and the roles of teachers and parents in developing it. The results indicate that low student self-confidence is influenced by internal factors, such as fear, anxiety, and lack of courage, as well as external factors, including family parenting styles, the social environment, and learning experiences at school. Teachers play a strategic role by providing emotional support, positive motivation, and implementing active learning strategies that encourage student engagement. Furthermore, parents play a crucial role in providing guidance, supportive parenting styles, and appropriate social stimulation. This study concludes that efforts to improve student self-confidence require consistent and ongoing collaboration between teachers and parents.